Memory and History of the Left: the organization of the working mass in São Paulo (Brazil) - Sousa, Rafael Lopes (2017)
The study of the left-wing party in the city of São Paulo is linked to the study of the labor movement in its more fundamental version - the syndicalism. The labor fights and the syndical struggle constituted the box of resonance of the of the revolutionary vanguard organization, that is, of the parties or movements which aspired the fall of the bourgeois order, announcing the social cohesion in the scope of the syndicates and of the national political parties. Although unquestionably under the influence of theorists and European parties, each left-wing movement was a prisoner of the Brazilian history, the history of São Paulo and, in last instance, of the personal relations established  among their participants. In this sense, the interactions of PCB with the national environment, studied as predeterminations for many activities and communist positions, must be summed to the bonds of friendship, which showed up as essential in the origins of the working class organization in our history.